EFISIENSI, EFEKTIVITAS DAN KONTRIBUSI SUB PAJAK DAERAH DI KABUPATEN MALUKU TENGGARA BARAT - Paulus Leliak; Gatot Sasongko (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
The purpose of this study was to determine the efficiency of local tax revenues, the contribution of sub-regional taxes to local taxes, the effectiveness of local tax revenues and sub-regional taxes. The research method is quantitative descriptive with secondary data from the Regional Revenue Agency in West Southeast Maluku Regency, West Southeast Maluku District Financial and Asset Management Agency and the Directorate General of Fiscal Balance of the Ministry of Finance of the Republic of Indonesia in 2012 - 2016. The result is inefficiencies in tax collection area. The highest sub-regional tax contributions are taxes on non-metal minerals and rocks, under restaurant tax and street lighting taxes. Regional tax effectiveness is categorized as less effective. The effectiveness of regional sub-tax namely hotel tax and tax on non-metal minerals and rocks is categorized as very effective; advertisement tax, street lighting tax and acquisition fee for land and building rights are categorized as quite effective; advertisement tax, entertainment tax and rural and urban land and building tax are categorized as ineffective.